Translating Irony: The Impact of Translation Techniques on Translation Quality in The Subtle Art of Not Giving a F*ck - Sakut Anshori; Arbain Arbain; Diana Hardiyanti; Abd. Rahman Zain (Universitas Islam Negeri Palopo, 2026)
This study aims to examine how translation techniques influence the rendering of ironic expressions in Mark Manson’s The Subtle Art of Not Giving a F*ck. While research on irony translation is growing, there is a lack of empirical evidence linking specific techniques to quality outcomes in non-fiction literature, representing a significant gap in current translation studies. Using a qualitative approach, this research identifies patterns of irony classification (Muecke, 1982), translation techniques (Molina & Albir, 2002), and quality assessment (Nababan et al., 2012) through content analysis and Focus Group Discussions. Findings reveal that while situational and verbal irony dominate the text, the effectiveness of translation techniques varies significantly; established equivalents, modulation, and transposition emerge as the most reliable techniques for maintaining high accuracy, acceptability, and readability. Conversely, techniques involving semantic shifts—such as amplification, adaptation, reduction, and discursive creation—often compromise the contradictory nuances essential to irony. By providing a systematic evaluation of these techniques, this study offers critical pedagogical implications for translator training and EFL instruction, emphasizing the necessity of linguistic and cultural competence in rendering irony.